José Martí and Paulo Freire: insertion in pedagogical insurgences in Latin America - Leite, Maria do Carmo Luiz Caldas (2022)
In order to bring together the thoughts of José Martí and Paulo Freire, the contributions to the Latin America educational ideas stand out. Two aspects are developed: a) the insertion of Freirian and Martian works in the history of the insurgencies, which are rooted in indignation in the face of injustice; b) the autochthony that reaffirms the culture adjusted to the Latin American reality, not imported from Europe and Anglo-Saxon America. Within the textual profusion of Martí and Freire, the choice turned to the construction of a bibliographical research. In conclusion, the relevance of these legacies in the midst of the radical nature of educational ideas is presented, highlighting common categories, including the freedom to reflect as a variant of the connection between theory and practice as well as of the school and life.